WASTE TO ENERGY (WTE) FOR THE SURVIVAL AND THE DEVELOPMENT - Ivanova, Nazmul Hossain (European Scientific Journal, ESJ, 2015)
The continuing interest to alternative sources of energy is increasing gradually as the world today is very much concern about rapidly growing population, global temperature rising and growing energy demand in short order. Energy is one of the most crucial components for economic, educational, science & technological development in the modern world. It is an integral part of every sphere of modern life and indispensible for almost all of the economic development ranging from farm irrigation to manufacturing of goods and heavy industrial activities. On the contrary, industrial growth is hindered, cost of products & services is intensive and economic growth and employment creation is limited if energy service is not highly reliable & of sufficient quality. On the other hand global warming, the increase in the temperature of the earth's neon-surface air, is the greatest challenge the world is confronting with and world grave concern for earth's all living creations. Every nation, including large & small, wealthy & poor, developed & developing, is under the impact of the ravage. The potential impact of global warming is devastative. It will affect hydrology and biology of earth-everything including economy, ecosystem and substances. Unusual acceleration of earth atmospheric greenhouse gas (GHG) emitted through massive combustion of fossil fuel and municipal solid waste (MSW) landfill is mainly responsible for this. Changing pattern of energy, for example, carbon neutral or carbon negative, easy accessible & cheap sources of energy only can confront the challenges the world is facing today with global warming, global climate changes and rapidly growing energy demand. Waste to energy (WTE) as a green & cheap source of energy could be a viable alternative.